2017
DOI: 10.1021/acs.chemrestox.7b00113
|View full text |Cite
|
Sign up to set email alerts
|

Nonsynonymous Polymorphisms in the Human AS3MT Arsenic Methylation Gene: Implications for Arsenic Toxicity

Abstract: Arsenic methylation, the primary biotransformation in the human body, is catalyzed by the enzyme As(III) S-adenosylmethionine (SAM) methyltransferases (hAS3MT). This process is thought to be protective from acute high-level arsenic exposure. However, with long-term low-level exposure, hAS3MT produces intracellular methylarsenite (MAs(III)) and dimethylarsenite (DMAs(III)), which are considerably more toxic than inorganic As(III) and may contribute to arsenic-related diseases. Several single nucleotide polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 51 publications
(171 reference statements)
0
16
0
Order By: Relevance
“…In this study, we characterized the effects of C. elegans natural genetic variation on physiological responses to the pervasive environmental toxin arsenic trioxide. Though the effects of this toxin have been extensively studied in a variety of systems (Ratnaike, 2003; Mandal and Suzuki, 2002; Bergquist et al, 2009; Paul et al, 2014; Shen et al, 2013), recent evidence from human population studies have revealed local adaptations within region-specific subpopulations (Schlebusch et al, 2015; Fujihara et al, 2009; Gomez-Rubio et al, 2010; Li et al, 2017). Our investigation into the natural variation in C. elegans responses to arsenic trioxide led to the discovery of a novel mechanism by which this compound could elicit toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we characterized the effects of C. elegans natural genetic variation on physiological responses to the pervasive environmental toxin arsenic trioxide. Though the effects of this toxin have been extensively studied in a variety of systems (Ratnaike, 2003; Mandal and Suzuki, 2002; Bergquist et al, 2009; Paul et al, 2014; Shen et al, 2013), recent evidence from human population studies have revealed local adaptations within region-specific subpopulations (Schlebusch et al, 2015; Fujihara et al, 2009; Gomez-Rubio et al, 2010; Li et al, 2017). Our investigation into the natural variation in C. elegans responses to arsenic trioxide led to the discovery of a novel mechanism by which this compound could elicit toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In human MDR1 (multidrug resistance 1), silent SNPs post-transcriptionally affected timing of cotranslational folding, resulted in altered structure of substrate and inhibitor interaction sites (Kimchi-Sarfaty et al 2007). In humans, nonsynonymous as3mt SNPs also changed arsenic-affinity and stability of as3mt through conformational structure changes of proteins, but not by changing gene expression (Li et al 2017).…”
Section: As3mt Expressionmentioning
confidence: 99%
“…Mutants with residue at 32 and 61 can still methylate MMA to DMA, but, mutants at 174 and 224 cannot take part in any of the two methylation steps [ 48 ]. With the discovery of new polymorphic sites in human AS3MTs [ 51 ], all eight mutant proteins showed decreased methylation activity in vitro due to among other factors, their low substrate affinity, and stability [ 52 ].…”
Section: Discovery Of the As3mt Gene And Proteimentioning
confidence: 99%